2018
DOI: 10.22261/jea.tnw2np
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic indices applied to biodiversity monitoring in a Costa Rica dry tropical forest

Abstract: Standardized methods for biodiversity monitoring are needed to evaluate conservation efforts. Acoustic indices are used in biodiversity assessments, but need to be compared to traditional wildlife methods. This work was conducted in the Santa Rosa National Park between June and November, 2015. We installed recorders and conducted bird point counts in twelve sampling sites. We compared acoustic indices (Acoustic Evenness Index [AEI], Acoustic Diversity Index [ADI], Acoustic Complexity Index [ACI], Bioacoustic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…4C ). Most studies tested more than one acoustic index (53%; Mammides et al ., 2017 ; Retamosa Izaguirre & Ramírez‐Alán, 2018 ; Eldridge et al ., 2018 ) and estimated diversity metrics from acoustic sources (68%). Over the environments and organisms investigated, research has mainly focused on terrestrial habitats (71%), birds (54%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4C ). Most studies tested more than one acoustic index (53%; Mammides et al ., 2017 ; Retamosa Izaguirre & Ramírez‐Alán, 2018 ; Eldridge et al ., 2018 ) and estimated diversity metrics from acoustic sources (68%). Over the environments and organisms investigated, research has mainly focused on terrestrial habitats (71%), birds (54%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to research results, the use of a single index does not always allow the relationship between its value and the species richness of birds. Therefore, some researchers have proposed the use of combinations of indices (Towsey et al, 2014;Retamosa Izaguirre et al, 2018). The integration of several acoustic parameters allowed to characterize and identify habitats with varying degrees of disturbance (mature forest, secondary growth and pasture) in Colombia (Gόmez et al, 2018) accurately predicted the diversity of birds in India (Buxton et al, 2018), etc.…”
Section: Discussionmentioning
confidence: 99%
“…ACI has shown mixed results regarding its ability as a bird indicator. Some studies found positive relationships between ACI and number of bird vocalizations (Pieretti et al, 2011), species richness and bird abundance (Eldridge et al, 2018;Retamosa et al, 2018), or bioacoustic activity in general (Towsey et al, 2014). Other studies found weak or negative relationships between ACI and species richness or biophonic activity (Mammides et al, 2017;Eldridge et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…amplified redundancy or song intensity) to offset noise masking effect. On the other hand, BIO has been tested in different environments, showing positive correlation with bird richness (Eldrigde et al, 2018), abundance (Retamosa et al, 2018), number of vocalizations (Pieretti et al, 2011) and biotic diversity (Fairbrass et al, 2017).…”
Section: Discussionmentioning
confidence: 99%